The non-connective tissue graft materials as an alternative treatment for gingival recession class I/II Miller - Nuraini Puspita Sari; Hasanuddin Thahir; Sri Oktawati (Makassar Dental Journal, 2020)
Objective: The aim of this systematic review is to evaluate effectiveness of non-connective tissue graft (CTG) materials, as alternative treatment for gingival recession (GR) class I/II Miller. Method: Articles searching was conducted on 2 online search engine, PubMed and Wiley. Articles are limited to publication between January 2015- November 2018, then manual iden-tification of journal accordance with inclusion criteria. The articles were divided into 2 groups, using non-CTG material and CTG. Result: From 160 publication items, there were 30 articles discusses about Non-CTG and CTG, but only 4 articles matching with inclusion criteria, there were 4 types of non CTG materials, for GR treatment. Each of these materials is com-pared with CTG. Conclusion: The non-CTG materials can be used as alternative treatment for GR class I/II Miller.